Neutrophils - Khajah, Maitham (IntechOpen, 2019)
This book highlights the numerous important properties of neutrophils and their role in various diseases, and as a possible therapeutic target as well. The first chapter briefly discusses the main effector neutrophil functions, which is followed by two chapters discussing the importance of different neutrophil receptors (cannabinoid and Fc?R) and their role in various disease conditions. The fourth chapter discusses the differential expression profile of CD16+CD11b+ on the surface of neutrophils as a tool for the diagnosis of acute infections. The last chapter discusses the physics of the NADPH oxidase system and the use of different chemiluminigenic probes for the detection of various reactive oxygen intermediates of the circulating neutrophils.